Hedging determinants of non-financial firms: A focus on UK Firms and the factors that determine their hedging decisions. - Francis, Kevin (2022)
The aim of this dissertation is to explore the factors that contribute to a firm’s Hedging decision in the United Kingdom. This dissertation builds upon previous studies in the field of hedging by incorporating established theories and investigating the validity of these theories using a new sample of 226 non-financial UK firms ranging from the year 2016 to 2021. This study finds that Financial distress costs are a major determinant of firm hedging along with factors like firm size and financial price risk.